FEASIBILITY AND READABILITY OF EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD) BASED MODULE ON GLOBAL WARMING MATERIAL GRADE VII - Siti Nurawaliyah; Shinta Purnamasari; Abdul Latip (Universitas Negeri Makassar, 2024)
This research and development (R&D) aimed at creating an Education for Sustainable Development (ESD) based module for seventh-grade global warming material that has good feasibility and readability. The research process involves preliminary studies, planning, draft development of the product, initial field trials, and revisions based on trial results. During the initial field trial stage, an assessment of the module's feasibility and readability was conducted. The data sources for this research include experts and students. Data collection was carried out using feasibility assessment sheets, readability question sheets, and readability questionnaires. The results of the module feasibility assessment yielded an average final score of 88.25%, interpreted as excellent. Similarly, the results of the module readability test showed an average final score of 88.44%, also interpreted as excellent.